Black market products confiscated in Norway 2011–2014 compared to analytical findings in urine samples. Issue 11 (26th November 2015) - Hullstein, Ingunn R.; Malerod‐Fjeld, Helle; Dehnes, Yvette; Hemmersbach, Peter
Abstract : Doping agents are widely and illicitly distributed through the Internet. Analysis of these preparations is useful in order to monitor the availability of prohibited substances on the market, and more importantly to predict which substances are expected to be found in urine samples collected from athletes and to aid clinical and forensic investigations. Based on a close collaboration with the Norwegian police and the Norwegian custom authorities, the Norwegian Doping Control Laboratory has performed analyses of confiscated material suspected of containing doping agents. The analyses were performed using gas chromatography (GC) and liquid chromatography (LC) combined with mass spectrometry (MS). The majority (67%) of the analyzed black market products contained anabolic‐ androgenic steroids (AAS) as expected, whereas peptide‐ and protein‐based doping substances were identified in 28% of the preparations. The Norwegian Doping Control Laboratory receives samples collected from recreational and elite athletes in addition to samples collected in clinical and forensic investigations. The findings in the seized material reflected the findings in the urine samples analyzed regarding the anabolic steroids. Thus, analyzing material seized in Norway may give a good indication of doping agents available on the local market. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Doping substances are readily available on the black market. A selection of confiscations suspected of containing prohibited compounds was analyzed by GC‐MS and LC‐MS/MS. When comparing these results with findings in urine samples from athletes and from clinical or forensic investigations, this study shows that analytical findings in confiscations may predict what to expect in samples submitted for doping analysis.